THE IMPORTANCE OF FAMILY MOTIVATION FOR STUDENT TO STUDY ONLINE DURING THE COVID-19 - Zesisca Nadya; Reza Pustika (Journal of English Language Teaching and Learning, 2021)
Covid-19 is a new type of disease that first attacked the city of Wuhan in China, a virus that has spread from person to person and this virus began to enter Indonesia in early March 2019 which made Indonesia have to lockdown activities outside the home including education because this virus spreads, So that the learning process for all students continues, the Indonesian government enforces the teaching and learning process to be carried out online or commonly called E-learning. In online learning, of course, students need motivation to support the student learning process. Internal motivation and external motivation are very important for the online learning process during the Covid-19 pandemic. This study investigates whether internal motivation and external motivation are very important for students learning online from home, and investigates whether family influences student motivation. In order to study online well during the Covid-19 pandemic, the target of this research is the seventh semester of English students. Educational study program at the Universitas Teknokrat Indonesia. There were 30 students who took part in this research. through distributing link questionnaires to Universitas Teknokrat Indonesia students. Keywords: motivation, family, covid-19, online learning, E-Learning.